Nova ureditev študentskega dela - Knez, Igor (Delavci in delodajalci, 2014)
The author introduces the Proposal of the Temporary and Occasional Work of Students Act. The first part of the contribution compares the current (legal) framework of student work with the upcoming regulatory framework. Through this the author emphasizes the most important points of the proposal, including the new restrictions and the interconnection with the employment legislation. In the second part the author focuses on the definition of the temporary and occasional work of students, and illustrates this definition through relevant court decisions and the open issues concerning this topic.
Keywords: delovno pravo; študenti; zaposlovanje